2015
DOI: 10.1091/mbc.e15-06-0330
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin's propensity for phase transition and its reorganization by dynamin-related protein 1 form a basis for mitochondrial membrane fission

Abstract: Fluid cardiolipin (CL) promotes self-assembly of Drp1, a dynamin-family GTPase involved in mitochondrial fission. Drp1 sequesters CL into condensed membrane platforms and in a GTP-dependent manner increases the propensity of the lipid to undergo a nonbilayer phase transition. CL reorganization generates local membrane constriction for fission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
183
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 74 publications
14
183
0
Order By: Relevance
“…1D). As expected from previous studies (Bustillo-Zabalbeitia et al, 2014; Macdonald et al, 2014; Montessuit et al, 2010; Stepanyants et al, 2015), Drp1 also preferentially bound liposomes containing a saturated CL. Although the exact role of this mitochondria specific phospholipid CL remains to be determined, binding to CL both stimulates the Drp1 GTPase activity that is required for mitochondrial division, and in a non-GTPase activity-dependent manner, enables cytochrome c release from mitochondria during apoptosis.…”
Section: Resultssupporting
confidence: 89%
“…1D). As expected from previous studies (Bustillo-Zabalbeitia et al, 2014; Macdonald et al, 2014; Montessuit et al, 2010; Stepanyants et al, 2015), Drp1 also preferentially bound liposomes containing a saturated CL. Although the exact role of this mitochondria specific phospholipid CL remains to be determined, binding to CL both stimulates the Drp1 GTPase activity that is required for mitochondrial division, and in a non-GTPase activity-dependent manner, enables cytochrome c release from mitochondria during apoptosis.…”
Section: Resultssupporting
confidence: 89%
“…In fact, the accompanying article (42) clearly shows that Mff stimulation of Drp1 activity is synergistic with CL stimulation. These results are congruent with previous reports of VD interactions with CL that promote Drp1 recruitment to lipid bilayers (21,(23)(24)(25). Given that CL has been shown to stabilize dimeric Drp1 at the lipid surface to promote Drp1 self-assembly (23), we propose that CL interactions at the membrane directly promote Drp1 dimer interactions with Mff (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro, the addition of negatively charged lipids increases Drp1 self-assembly to form larger helical assemblies that represent the contractile apparatus of mitochondrial fission (20), and these functional polymers exhibit stimulated GTPase activity (14,(21)(22)(23). The VD has recently been shown to act as a negative regulator of Drp1 self-assembly (14) with an inherent ability to interact with cardiolipin (CL) present in mitochondrial membranes (21,(23)(24)(25). Studies in yeast have shown that the VD is required for interactions with a mitochondrial adaptor protein (26), but the partner protein identified in that study is not conserved in higher eukaryotes, which suggests that the role of the VD may have evolved in higher organisms to accommodate different regulatory interactions in the cytosol and at the surface of mitochondria.…”
mentioning
confidence: 99%
“…The importance of CL microdomains is of relevance during initiation of apoptosis, where caspase 8 is thought to localize to CL microdomains that would be spatially distributed at contact sites between the inner and outer mitochondrial membranes [71]. In another study, fission proteins were also reported to be associated with CL microdomains [72]. However, any conclusions about the existence of CL microdomains must account for the methodology used for isolating these membrane fractions, which may promote artifacts [73].…”
Section: 0 Discussionmentioning
confidence: 99%